Information needs of oncologists, general practitioners and other professionals caring for patients with cancer. (23rd August 2016) - Ciarlo, G.; Liebl, P.; Zell, J.; Fessler, J.; Koester, M.J.; Ruetters, D.; Mugele, K.; Huebner, J.
Abstract : Oncology is a rapidly developing field with a growing number of publications every year. The main goal of this survey was to learn more about the information needs of oncologists and general practitioners. Data were collected using a standardised questionnaire developed in collaboration with the German Cancer Society (Deutsche Krebsgesellschaft) and the German Association of General Practitioners (Deutscher Hausärzteverband). A total of 495 questionnaires could be evaluated. Medical congresses were the preferred source of information for all participants. General practitioners preferred textbooks, while oncologists preferred journals and the Internet (all p  <   .001). Reasons for a lack of confidence during patient consultation were lack of time (60% of participants), lack of knowledge (61% of general practitioners and 26% of oncologists) and lack of data (>50%). Oncologists felt more confident in searching scientific databases than general practitioners did. Both groups required rapid access to transparent information. For general practitioners, reviews and comments by experts helped to put new information in the context of cancer treatment. Oncologists and general practitioners showed significantly different information needs and different ways to access specific information. In order to better integrate general practitioners while simultaneously serving the needs of oncologists, a database that is up to date, rapidly accessible and does not incur high costs would be helpful.